Manajemen Nyeri, Pencegahan Infeksi, dan Mobilisasi Dini Pada Pasien Pasca Apendektomi di RS Bhayangkara Brimob: Studi Kasus - Eko Sukarno; Agustini Liviana Dwi Rahmawati (Politeknik Karya Husada, 2025)
Background: Appendectomy involves surgical incision and tissue injury, which may cause postoperative pain. In addition to pain, patients undergoing appendectomy are at risk of infection and impaired physical mobility due to pain and concerns regarding the surgical wound. Objective: To describe the implementation of pain management, infection prevention, and early mobilization in post-appendectomy patients at the third floor of Bhayangkara Brimob Hospital. Methods: This study used a descriptive design with a case study approach involving two post-appendectomy patients, Mrs. R and Ms. B. Data were collected through interviews, observation, physical examination, and nursing documentation. Nursing care was provided for 3 × 24 hours through assessment, nursing diagnosis, planning, implementation, and evaluation. Results: The nursing diagnoses identified in both patients were acute pain, risk for infection, and impaired physical mobility. The interventions included pain management using deep-breathing relaxation techniques, infection prevention through wound monitoring and hygiene education, and gradual early mobilization. After 3 × 24 hours, Mrs. R’s pain score decreased from 6 to 3, while Ms. B’s pain score decreased from 5 to 2. No signs of infection were observed in either patient, and both patients demonstrated improved mobility, including the ability to walk to the bathroom independently. Conclusion: The implementation of pain management, infection prevention, and early mobilization for 3 × 24 hours produced positive outcomes in both post-appendectomy patients. All three nursing problems were resolved, and nursing interventions were discontinued when the patients were discharged. Keywords: acute pain; appendectomy; case study; impaired physical mobility; risk for infection